Immune modulations and survival strategies of evolved hypervirulent Salmonella Typhimurium strains - Pradhan, Diana; Pradhan, Jasmin; Mishra, Abtar; Karmakar, Kapudeep; Dhiman, Rohan; Chakravortty, Dipshikha; Negi, Vidya Devi (Biochimica et biophysica acta. General subjects, 2020)
Evolving multidrug-resistance and hypervirulence in Salmonella is due to multiple host-pathogen, and non-host environmental interactions. Previously we had studied Salmonella adaptation upon repeated exposure in different in-vitro and in-vivo environmental conditions. This study deals with the mechanistic basis of hypervirulence of the passaged hypervirulent Salmonella strains reported previously. Real-time PCR, flow cytometry, western blotting, and confocal microscopy were employed to check the alteration of signaling pathways by the hypervirulent strains. The hypervirulence was also looked in-vivo in the Balb/c murine model system. The hypervirulent strains altered cytokine production towards anti-inflammatory response via NF-κB and Akt-NLRC4 signaling in RAW-264.7 and U-937 cells. They also impaired lysosome number, as well as co-localization with the lysosome as compared to unpassaged WT-STM. In Balb/c mice also they caused decreased antimicrobial peptides, reduced nitric oxide level, altered cytokine production, and reduced CD4+ T cell population leading to increased organ burden. Hypervirulent Salmonella strains infection resulted in an anti-inflammatory environment by upregulating IL-10 and down-regulating IL-1β expression. They also evaded lysosomal degradation for their survival. With inhibition of NF-κB and Akt signaling, cytokine expression, lysosome number, as well as the bacterial burden was reverted, indicating the infection mediated immune modulation by the hypervirulent Salmonella strains through these pathways. Understanding the mechanism of adaptation can provide better disease prognosis by either targeting the bacterial gene or by strengthening the host immune system that might ultimately help in controlling salmonellosis. •The hypervirulent strains impaired lysosome number and bacterial fusion with the lysosome.•The infection resulted in an anti-inflammatory environment by altering cytokine expression.•The hypervirulent strains modulated host NF-κB and Akt signaling.•They proliferated more in Balb/c mice by modulating innate and adaptive parameters.